Use of brand management for the czech railways long-distance trains from the marketing perspective - Chocholáč, Jan; Kudláčková, Nina; Hruška, Roman; Salava, Daniel (University of Pardubice, 2018)
Brand Management is a very important from the perspective of businesses because it helps businesses communicate with the target market. Brand management consists of tangible elements (product, design, packaging etc.) and intangible elements (customer experience and relationship with the brand). The Czech Railways company use brand management for specific long-distance train lines like for example “Metropolitan”, “Západní expres”, “Slovácký expres” or “Jižní expres”. The aim of the article is to analyse the use of Brand Management for long-distance train lines of Czech Railways and evaluate customer survey results.
Keywords: brand management; czech railways; metropolitan; Západní expres; Slovácký expres; Jižní expres